Dialogue of Civilizations: An Introduction to Civilizational Analysis - Sivaramkrishna, M (Journal of Dharma, 2001)
Victor Segesvary, Dialogue of Civilizations: An Introduction to Civilizational Analysis; Boston: University Press of America; pp. 132; Cloth 49.00: paper27.50.